Students’ Perceptions Toward the Implementation of Quipper School as an E-Learning Platform in Teaching English - Santi Septinawati; R. Bunga Febriani; Wawan Tarwana; Syafryadin Syafryadin (Jadila: Journal of Development and Innovation in Language and Literature Education, 2020)
This article reports the students’ perceptions in implementing Quipper School as an e- learning platform in teaching English and to know the advantages and disadvantages of it. This study took two sample classes with the overall fifty-three students by using cluster sampling technique and focusing on the survey study method. Twenty questionnaires provided to identify the students’ perceptions about quipper school. A depth information appear to be as important to gain more information and continuous responses to explore the advantages and disadvantages of implementing quipper school that have been undertaken by interviewing the students. The findings revealed that the students are comfortable learning with technology and also prefer to use IT. More significantly, The advantages of quipper school keep interaction between teacher and student in and out of the classroom, students still get lesson or review the material even though the teacher is not present in the classroom, and enhances students’ learning experiences using new learning system. Besides, quipper school also has disadvantages when it is applied in learning process, such as unstable internet connections, limited facilities (computer) that support learning by using quipper school, and there was no speaking material which it could be implemented in quipper school. It can be noted today learning and teaching can benefit from using quipper school in teaching English, students still get a lesson even though the teacher is not present to provide direct instruction and students can improve their achievement in learning English by reviewing the material wherever and whenever they are.